Implementation of Continuing Professional Development for Health Professionals in Nepal - Dangal, Ganesh; Koirala, Sushil; Chapagain, Sandhya; Sharma, Shashi; Adhikari, Ramesh Kant; Shah, Ankur (Journal of Nepal Health Research Council, 2020)
Continuing Medical Education (CME) is the educational activities that serve to maintain, develop, or increase the knowledge, skills, and professional performance and relationships a physician uses to provide services for patients, the public, or the profession. Typically, Continuing Professional Development (CPD), or Continuing Physician Professional Development (CPPD) includes all activities that doctors undertake, formally and informally, including CME, in order to maintain, update, develop, and enhance their knowledge, skills, and attitudes in response to the needs of their patients. In other words, continuing professional development is any learning outside of undergraduate or postgraduate training or education that helps us maintain and improve our performance. CPD mainly encompasses self-directed and practice-based learning activities in addition to supervised education or training. CPD designates the period of education and training of doctors or health care providers commencing after completion of both basic and postgraduate medical education, thereafter extending throughout each one’s professional life. The value and importance of CME and CPD are self-evident to every doctors and health care providers. CME-CPD actually starts early on in our career but the actual importance of CME-CPD is most relevant after specialization which may be years long in a doctor’s life. <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 370.2040273437499px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(0.9602747826723522);"> Continuing Medical Education (CME) is the educational activities that serve to maintain, develop, or increase the knowledge, skills, and professional performance and relationships a physician uses to provide services for patients, the public, or the profession. Typically, Continuing Professional Development (CPD), or Continuing Physician Professional Development (CPPD) includes all activities that doctors undertake, formally and informally, including CME, in order to maintain, update, develop, and enhance their knowledge, skills, and attitudes in response to the needs of their patients.1 In other words, continuing professional development is any learning outside of undergraduate or postgraduate training or education that helps us maintain and improve our performance. CPD mainly encompasses self-directed and practice-based learning activities in addition to supervised education or training. CPD designates the period of education and training of doctors or health care providers commencing after completion of both basic and postgraduate medical education, thereafter extending throughout each one’s professional life.2 The value and importance of CME and CPD are self-evident to every doctors and health care providers. CME-CPD actually starts early on in our career but the actual importance of CME-CPD is most relevant after specialization which may be years long in a doctor’s life. <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 370.2040273437499px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(0.9602747826723522);"> <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 370.2040273437499px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(0.9602747826723522);"> Continuing Medical Education (CME) is the educational activities that serve to maintain, develop, or increase the knowledge, skills, and professional performance and relationships a physician uses to provide services for patients, the public, or the profession. Typically, Continuing Professional Development (CPD), or Continuing Physician Professional Development (CPPD) includes all activities that doctors undertake, formally and informally, including CME, in order to maintain, update, develop, and enhance their knowledge, skills, and attitudes in response to the needs of their patients.1 In other words, continuing professional development is any learning outside of undergraduate or postgraduate training or education that helps us maintain and improve our performance. CPD mainly encompasses self-directed and practice-based learning activities in addition to supervised education or training. CPD designates the period of education and training of doctors or health care providers commencing after completion of both basic and postgraduate medical education, thereafter extending throughout each one’s professional life.2 The value and importance of CME and CPD are self-evident to every doctors and health care providers. CME-CPD actually starts early on in our career but the actual importance of CME-CPD is most relevant after specialization which may be years long in a doctor’s life. Continuing Medical Education (CME) is the educational <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 391.03736067708326px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0844166805117128);">activities that serve to maintain, develop, or increase <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 411.8706940104166px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.01251521979407);">the knowledge, skills, and professional performance and <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 432.7040273437499px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(0.9957123651546352);">relationships a physician uses to provide services for <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 453.53736067708326px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0771663524477302);">patients, the public, or the profession. Typically, Con <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 490.55516666666665px; top: 453.53736067708326px; font-size: 14.999999999999998px; font-family: sans-serif;">- <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 474.3706940104166px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0307840808591282);">tinuing Professional Development (CPD), or Continuing <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 495.2040273437499px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(0.9437383981133092);">Physician Professional Development (CPPD) includes all <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 516.0373606770833px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0389205630580016);">activities that doctors undertake, formally and informal <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 490.55516666666665px; top: 516.0373606770833px; font-size: 14.999999999999998px; font-family: sans-serif;">- <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 536.8706940104166px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0200433044871167);">ly, including CME, in order to maintain, update, develop, <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 557.70402734375px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0220858658948384);">and enhance their knowledge, skills, and attitudes in re <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 490.55516666666665px; top: 557.70402734375px; font-size: 14.999999999999998px; font-family: sans-serif;">- <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 578.5373606770834px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0310427248637866);">sponse to the needs of their patients. Continuing Medical Education (CME) is the educational <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 391.03736067708326px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0844166805117128);">activities that serve to maintain, develop, or increase <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 411.8706940104166px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.01251521979407);">the knowledge, skills, and professional performance and <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 432.7040273437499px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(0.9957123651546352);">relationships a physician uses to provide services for <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 453.53736067708326px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0771663524477302);">patients, the public, or the profession. Typically, Con <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 490.55516666666665px; top: 453.53736067708326px; font-size: 14.999999999999998px; font-family: sans-serif;">- <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 474.3706940104166px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0307840808591282);">tinuing Professional Development (CPD), or Continuing <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 495.2040273437499px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(0.9437383981133092);">Physician Professional Development (CPPD) includes all <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 516.0373606770833px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0389205630580016);">activities that doctors undertake, formally and informal <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 490.55516666666665px; top: 516.0373606770833px; font-size: 14.999999999999998px; font-family: sans-serif;">- <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 536.8706940104166px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0200433044871167);">ly, including CME, in order to maintain, update, develop, <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 557.70402734375px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0220858658948384);">and enhance their knowledge, skills, and attitudes in re <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 490.55516666666665px; top: 557.70402734375px; font-size: 14.999999999999998px; font-family: sans-serif;">- <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 578.5373606770834px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0310427248637866);">sponse to the needs of their patients. Continuing Medical Education (CME) is the educational <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 391.03736067708326px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0844166805117128);">activities that serve to maintain, develop, or increase <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 411.8706940104166px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.01251521979407);">the knowledge, skills, and professional performance and <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 432.7040273437499px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(0.9957123651546352);">relationships a physician uses to provide services for <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 453.53736067708326px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0771663524477302);">patients, the public, or the profession. Typically, Con <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 490.55516666666665px; top: 453.53736067708326px; font-size: 14.999999999999998px; font-family: sans-serif;">- <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 474.3706940104166px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0307840808591282);">tinuing Professional Development (CPD), or Continuing <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 495.2040273437499px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(0.9437383981133092);">Physician Professional Development (CPPD) includes all <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 516.0373606770833px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0389205630580016);">activities that doctors undertake, formally and informal <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 490.55516666666665px; top: 516.0373606770833px; font-size: 14.999999999999998px; font-family: sans-serif;">- <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 536.8706940104166px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0200433044871167);">ly, including CME, in order to maintain, update, develop, <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 557.70402734375px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0220858658948384);">and enhance their knowledge, skills, and attitudes in re <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 490.55516666666665px; top: 557.70402734375px; font-size: 14.999999999999998px; font-family: sans-serif;">- <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; left: 118.11016666666666px; top: 578.5373606770834px; font-size: 14.999999999999998px; font-family: sans-serif; transform: scaleX(1.0310427248637866);">sponse to the needs of their patients.